Partial Recurrent Laryngeal Nerve Paralysis or Paresis? In Search for the Accurate Diagnosis - Alexander Delides; Panagiotis Kokotis; Pavlos Maragoudakis (Case Reports in Otolaryngology)
“Partial paralysis” of the larynx is a term often used to describe a hypomobile vocal fold as is the term “paresis.” We present a case of a dysphonic patient with a mobility disorder of the vocal fold, for whom idiopathic “partial paralysis” was the diagnosis made after laryngeal electromyography, and discuss a proposition for a different implementation of the term.